Toward the accurate prediction of soot in engine applications. (September 2019) - Gao, Jian; Kuo, Tang-Wei
Soot emissions from internal combustion engines represent a major challenge to engine manufactures with ever most stringent emission regulations, not only in soot mass yielded but also in soot particle number. For example, a particulate number standard has been introduced in 2011 with Euro 5b for diesel engines and in 2014 with Euro 6 for petrol engines (a limit of 6 × 10 11 /km). Soot models provide a detailed insight into soot evolution processes and are thus an essential tool in today's advanced engine designs. Therefore, continuous efforts are made to develop more physically based engine soot models and improve the prediction accuracy. The primary objective of this work is to identify and demonstrate the critical parameters for accurate soot predictions in internal combustion engine applications using the high-fidelity detailed soot model from an engineering point of view. A detailed soot model based on sectional method was used to solve the soot process in diesel and spark ignition direct injection gasoline engines. A series of sensitivity analyses were carried out to evaluate the importance and significance of wall boundary conditions, wall film formation and vaporization, multi-component fuel surrogate, and soot transport process in engine exhaust on soot predictions. The predicted results were compared in details to engine-out measurements in terms of soot mass, number density, and size distributions under various operating conditions. The model results demonstrate that the correct description of the spray–wall interaction and wall film vaporization, as well as the soot transport processes in full engine cycle, is critical for achieving reliable predictive capabilities in engine simulations, especially for spark ignition direct injection gasoline engines. The findings should help engineers in this field for more accurate soot predictions in engine simulations.